Dynamic covalent conjugated polymer epitaxy on graphene. Issue 39 (25th September 2019) - Assies, Lea; Fu, Chaoying; Kovaříček, Petr; Bastl, Zdeněk; Drogowska, Karolina A.; Lang, Jan; Guerra, Valentino L. P.; Samorì, Paolo; Orgiu, Emanuele; Perepichka, Dmitrii F.; Kalbáč, Martin
Abstract : Covalently dynamic polymers self-assemble on graphene crystalline epitaxial layers to for 2-D heterostructures. Abstract : Hybrid heterostructures formed from ordered molecular layers on two-dimensional materials can have unique properties differing from those of their bulk phases. By employing principles of dynamic covalent chemistry, we have synthesized a series of novel conjugated polyimines that form epitaxial ordered monolayers on graphene. The interplay between molecular physisorption and dynamic polymerization at the solid–liquid interface drives the formation of longer chains at the surface with dramatically higher rates than in solution. The physico-chemical properties of such assemblies at different length scales on graphene were investigated by a combination of experimental techniques. 'Covalent dynamic epitaxy' was also found to modulate the properties of both substrate and dynamers such as doping and photoluminescence, respectively.